2012
DOI: 10.1080/15299732.2011.641497
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Severity and Defensive Emotion-Regulation Reactions as Predictors of Forgetting Childhood Trauma

Abstract: Using a retrospective survey, we studied a sample of 1,679 college women to determine whether reports of prior forgetting of childhood sexual abuse, physical abuse, and other traumas could be explained by trauma severity and individual differences in the use of defensive emotion-regulation reactions (i.e., repressive coping, dissociation, and fantasy proneness). Among victims of physical abuse (but not sexual abuse or other types of trauma), those who experienced severe abuse and used defensive reactions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
(73 reference statements)
2
6
0
Order By: Relevance
“…note that this rate is quite consistent with past and similar large-scale non clinical survey or prospective studies; for example, Bottoms et al, 2012, Epstein & Bottoms, 2002Goodman et al, 2003;Melchert, 1996). Our sample may not be representative of French people over the age of 18, so we cannot make a precise extrapolation of the number of people this might involve.…”
Section: Reports Of Recovered Memoriessupporting
confidence: 88%
See 2 more Smart Citations
“…note that this rate is quite consistent with past and similar large-scale non clinical survey or prospective studies; for example, Bottoms et al, 2012, Epstein & Bottoms, 2002Goodman et al, 2003;Melchert, 1996). Our sample may not be representative of French people over the age of 18, so we cannot make a precise extrapolation of the number of people this might involve.…”
Section: Reports Of Recovered Memoriessupporting
confidence: 88%
“…Using careful follow‐up questions to the initial question about recovered memories, we found that 9% of the participants who reported child abuse reported having recovered an abuse memory that they did not previously know about nor remember (2.5% of the total sample). This rises to 23% of this subsample (6.3% of the total sample) if we add the participants who had knowledge of abuse; note that this rate is quite consistent with past and similar large‐scale non clinical survey or prospective studies; for example, Bottoms et al, 2012, Epstein & Bottoms, 2002; Goodman et al, 2003; Melchert, 1996). Our sample may not be representative of French people over the age of 18, so we cannot make a precise extrapolation of the number of people this might involve.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Following the study by Wilson and Barber (1983), many researchers ascribed the genesis of fantasy proneness to adverse childhood experiences and trauma-related psychopathology, particularly dissociative symptoms, and argued that fantasy proneness is fueled by a need to escape adverse childhood experiences and functions as an automatized habitual defensive FANTASY PRONENESS: A META-ANALYSIS reaction (e.g., Bottoms et al, 2012Bottoms et al, , 2016Lawrence et al, 1995). Kluemper and Dalenberg (2014), for example, contended that fantasy proneness and dissociative symptomatology overlap because both originate from a traumatic history and both involve absorption (i.e., a state of strong attentional focus), which could be construed as a mental flight from aversive memories (see also Allen & Coyne, 1995).…”
Section: Traumamentioning
confidence: 99%
“…Building on this work, using emotion language in a trauma narrative might accomplish a similar goal as exposure therapy and affect labeling by encouraging people to reflect on and engage with their emotional responses to the trauma. Moreover, given that people who have experienced severe trauma may be especially likely to attempt to avoid their traumatic memories (Bottoms, Najdowski, Epstein, & Badanek, 2012), those who have experienced severe trauma may have the most to gain from the expression of emotion—both positive and negative—in their trauma narratives.…”
Section: Benefits Of Confronting Emotions For Trauma Survivorsmentioning
confidence: 99%